Factors associated with hospitalizations due to non-communicable chronic diseases in older adults (Research, Society and Development, 2025)
Objective: To analyze associated factors with hospitalizations of elderly people due chronic non-communicable diseases (NCDs), evaluate the interference of the number of NCDs and the impact of a sedentary lifestyle on admissions to a public hospital in the city of Guarulhos, Brazil. Method: Cross-sectional, observational study, convenience sample composed by patients hospitalized in the clinical wards of Complexo Hospitalar Padre Bento de Guarulhos (CHPBG- Padre Bento Hospital). A questionnaire developed by the authors based on similar studies was applied to people aged 60 years or over diagnosed with NCDs hospitalized due to their complications. All patients were residents on the city of Guarulhos and exclusively users of the Public Health System. The results were classified on a parity basis and the Odds Ratio (OR) was used for the main analyses. Results: Between 90 patients, all of them were sedentary and with average of 3 NCDs. We observed an association between the number of NCDs and more chances of hospitalizations (OR=3.48, p